Weaving the Braid of Culturally Responsive Leadership Within Policy and Governance to Improve Indigenous Student Success - Niemi, Shelly L (Scholarship@Western, 2020)
This Organizational Improvement Plan (OIP) explores a Problem of Practice (PoP) that highlights the need for why the Board of Education and the Senior Administration team within the Raven Bay School Division (RBSD, pseudonym) would benefit from using a culturally responsive leadership approach when making decisions and how this may be achieved through policy and governance to guide their practice. The goal of this OIP is to examine why this leadership approach would be relevant for the Board of Education and the Senior Leadership team when they are making any policy and governance decisions, as it relates to Indigenous Education and how this leadership approach could positively support the improvement of educational outcomes and opportunities for Indigenous learners across the RBSD. The recommended solutions found within this OIP are intended to show how the RBSD can weave together a culturally responsive braid of policy and governance to address their goal of improving Indigenous learner outcomes found within their strategic. If this OIP is implemented, the solutions could be turned into strategies that work towards positively closing the current achievement gap that exists between Indigenous and non-Indigenous learners within the RBSD. Thus, beginning to shift the negative narrative of the culture of low expectations for Indigenous learners within the RBSD to a positive narrative of equity and success through the lens of culturally responsive leadership. Keywords: Aboriginal, Aboriginal Learning, Aboriginal Rights, Assimilation, Colonization, Culture, Decolonization, Educator, Emotional Intelligence, Ethical, Experiential Learning, First Nations, First Peoples, Holistic Education, Indigenizing Education, Lifelong Learning, Reconciliation, Social Emotional Learning, Transformative Change, Worldview